Why do guidelines recommend screening for abdominal aortic aneurysms, but not for asymptomatic carotid stenosis? A plea for a randomized controlled trial. (15th January 2023) - Paraskevas, Kosmas I.; Spence, J. David; Mikhailidis, Dimitri P.; Antignani, Pier Luigi; Gloviczki, Peter; Eckstein, Hans-Henning; Spinelli, Francesco; Stilo, Francesco; Saba, Luca; Poredos, Pavel; Dardik, Alan; Liapis, Christos D.; et al.
Abstract: Background: Current guidelines do not recommend screening for asymptomatic carotid artery stenosis (AsxCS). The rationale behind this recommendation is that detection of AsxCS may lead to an unnecessary carotid intervention. In contrast, screening for abdominal aortic aneurysms is strongly recommended. Methods: A critical analysis of the literature was performed to evaluate the implications of detecting AsxCS. Results: Patients with AsxCS are at high risk for future stroke, myocardial infarction and vascular death. Population-wide screening for AsxCS should not be recommended. Additionally, screening of high-risk individuals for AsxCS with the purpose of identifying candidates for a carotid intervention is inappropriate. Instead, selective screening for AsxCS should be considered and should be viewed as an opportunity to identify individuals at high risk for atherosclerotic cardiovascular disease and future cardiovascular events for the timely initiation of intensive medical therapy and risk factor modification. Conclusions: Although mass screening should not be recommended, there are several arguments suggesting that selective screening for AsxCS should be considered. The rationale supporting such selective screening is to optimize risk factor control and to initiate intensive medical therapy for prevention of future cardiovascular events, rather than to identify candidates for an intervention. Highlights: Patients with asymptomatic carotid stenosis are at high risk of future stroke, myocardial infarction and vascular death. Selective screening for asymptomatic carotid stenosis should be considered to reduce cardiovascular events. Early identification of patients with asymptomatic carotid stenosis would enable timely initiation of preventive measures.